Monetary union and macroeconomic stabilization - Dominik Groll (Kiel Institute for the World Economy (IfW), 2013)
It is conventionally held that countries are worse off by forming a monetary union when it comes to macroeconomic stabilization. However, this conventional view relies on assuming that monetary policy is conducted optimally. Relaxing the assumption of optimal monetary policy not only uncovers that countries do benefit from forming a monetary union under fairly general conditions. More importantly, it also reveals that a monetary union entails the inherent benefit of stabilizing private-sector expectations about future inflation. As a result, inflation rates are more stable in a monetary union.
More recent version: http://hdl.handle.net/10419/126153
Keywords: F33; F41; E52; 330; monetary union; macroeconomic stabilization; welfare analysis; history dependence; inflation expectations